2016
DOI: 10.3233/jad-150096
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Prodromal Alzheimer’s Disease, a Retrospective Study of 13 New Cases: Expanding the Spectrum of Alzheimer’s Disease to an Epileptic Variant?

Abstract: Our data, in conjunction with those of the 12 previously described subjects, suggest the existence of a currently unrecognized inaugural epilepsy syndrome of sporadic AD. Such a syndrome could be called the epileptic variant of AD because seizures are its sole feature for more than 2.5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 14 publications
7
79
0
1
Order By: Relevance
“…Studies have shown that seizures related to AD may precede or coincide with the onset of the cognitive decline (35). Our three cases suggest that elderly onset temporal epileptic auras may be a presenting symptom of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that seizures related to AD may precede or coincide with the onset of the cognitive decline (35). Our three cases suggest that elderly onset temporal epileptic auras may be a presenting symptom of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures are prevalent in around 28% of cases with AD and were long thought mostly to be a late manifestation of the disease process with the progression of neurodegeneration (2). However, more recent studies have revealed that in some cases, seizures related to AD may precede or coincide with the onset of the cognitive changes (35). Neuroimaging studies in patients with mild cognitive impairment (MCI) have highlighted hippocampal hyperactivation on fMRI (6), and treatment with the anti-seizure medication levetiracetam targeting this hyperactivation was found to improve memory task performance (7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, disturbed activity may contribute to the development of cognitive violations: epileptiform and rhythmic abnormalities in the temporal regions (in particular in the hippocampus) can cause amnestic disorders, which were reduced by antiepileptic drug treatment (Gallassi, 2006; Bakker et al, 2012). In patients with seizures in combination with AD, a case series from California with so called “vu/déjà vu” phenomena was described (Vossel et al, 2013), while another series from France (Cretin et al, 2016) had some cases that were termed “epileptic prodromal AD.” The authors believed that there is an epileptic version of AD, which usually starts with seizures as an initial symptom followed by cognitive deficit. Similar signs of cognitive and behavioral impairments in TLE and AD have been recently described by Chin and Scharfman (2013).…”
Section: Electro-clinical Data For Patients With “Epileptic Prodromalmentioning
confidence: 99%
“…Adult-onset epilepsy of unknown cause could thus represent a risk factor for the ongoing neurodegenerative damage, even when epileptic manifestations and clinically recognized dementia are separated by long time (Cretin et al, 2016; Sarkis et al, 2017). …”
Section: Electro-clinical Data For Patients With “Epileptic Prodromalmentioning
confidence: 99%
“…AD patients, including those with familial AD, are at increased risk for epileptic seizures, and recent findings suggest a very high incidence of sub-clinical epileptiform activity in AD (Born, 2015). Data from longitudinal human studies suggest that neuronal hyperexcitability occurs before cognitive impairment (Cretin et al, 2016). Early cell culture studies demonstrated that pathogenic forms of Aβ (Mattson et al, 1992) and tau (Furukawa et al, 2003) perturb neuronal calcium homeostasis, which can render neurons vulnerable to excitotoxicity, while subsequent studies showed that neurons in transgenic mice that express AD-causing APP, presenilin 1, or tau mutations exhibit vulnerability to excitotoxicity (Decker et al, 2016; Guo et al,1999; Hall et al, 2015; Palop et al, 2007).…”
Section: Introductionmentioning
confidence: 99%